Are separated/divorced same sex families more likely to establish equal coparenting? A preliminary outcome from a court‐based program. (10th September 2022) - Zhu, Tianmei; Alschech, Jonathan; Pruett, Marsha Kline
Abstract: In this article, we examine the impact of inconsistent laws and possible judicial bias on children's opportunities to experience interaction and support from all parents, when those same parents separate/divorce. The Family Resolutions Specialty Court (FRSC) in Massachusetts provides a model through which procedures support all parents and minimize bias by engaging parental involvement collaboratively. Using exploratory data collected and analyzed from separated/divorced same sex and heterosexual parenting plans developed by families in FRSC (N = 50; 86% heterosexual, 14% same sex), we examine children's living arrangements regarding daytime parenting time and the number of overnights with the non‐primary parent, as well as the consistency of parenting schedules. Results identified a tendency among same sex parents to establish parenting plans that were more equal between partners and consistent across weeks. This small study adds to the emerging literature exploring coparenting among same sex parents post‐separation/divorce by contextualizing this preliminary finding and setting the stage for more rigorous analysis of differences in parenting plans and coparenting post separation/divorce between heteronormative and queer families. Key points for the family court community: Separating same sex parents appearing in family courts are still too often facing systems and professionals guided by heteronormative values and beliefs. In separated/divorcing same sex families, the non‐biological parent is vulnerable to maintaining their parenting status. In this small, preliminary study, same sex parents were found to be more likely than heterosexual families to develop consistent weekly schedules, these included more daytime parenting time and more overnights. The FRSC program in Massachusetts exemplifies an intervention strategy that facilitates coparenting plans while avoiding heteronormative and gendered biases identified. Future research is needed that provides more evidence focusing on the unique challenges same sex parnts face when separating/divorcing.